2009
DOI: 10.1074/jbc.m805606200
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Protein Kinase A Activity during Cell Migration Is Mediated by A-kinase Anchoring Protein AKAP Lbc

Abstract: Protein kinase A (PKA) has been suggested to be spatially regulated in migrating cells due to its ability to control signaling events that are critical for polarized actin cytoskeletal dynamics. Here, using the fluorescence resonance energy transfer-based A-kinase activity reporter (AKAR1), we find that PKA activity gradients form with the strongest activity at the leading edge and are restricted to the basal surface in migrating cells. The existence of these gradients was confirmed using immunocytochemistry u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 64 publications
3
63
0
Order By: Relevance
“…In our recent analysis of transcriptional changes mediated by integrin ␣ 6 ␤ 4 in these cells, we find that AKAP-Lbc mRNA expression is upregulated in MDA/␤ 4 cells 2.5-fold over control cells (4). To determine whether AKAPLbc is the Rho GEF responsible for RhoA activation in the MDA/␤ 4 transfectants, we reduced AKAP-Lbc by two separate siRNAs as done previously (39), plated cells on collagen coated dishes, stimulated cells with 100 nM LPA, and then assessed cell lysates for RhoA activity and AKAP-Lbc expression. As shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In our recent analysis of transcriptional changes mediated by integrin ␣ 6 ␤ 4 in these cells, we find that AKAP-Lbc mRNA expression is upregulated in MDA/␤ 4 cells 2.5-fold over control cells (4). To determine whether AKAPLbc is the Rho GEF responsible for RhoA activation in the MDA/␤ 4 transfectants, we reduced AKAP-Lbc by two separate siRNAs as done previously (39), plated cells on collagen coated dishes, stimulated cells with 100 nM LPA, and then assessed cell lysates for RhoA activity and AKAP-Lbc expression. As shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Suspended cells (3 ϫ 10 6 ) were electroporated with 200 nM control small interfering (si)RNA (nontargeting; Dharmacon) or individual siRNAs specific for AKAP-Lbc (AKAP13) as reported previously (39). Individual sequences for AKAP-Lbc are 5=-UCAACAGACUCAC-UAAAUAUU-3= (number 3) and 5=-GGAAGAAGCUUGUACGU-GAUU-3= (number 5).…”
Section: Methodsmentioning
confidence: 99%
“…PKA is required for the starvation-induced aggregation of Dictyostelium cells (Mann and Firtel, 1991;Mann et al, 1997), a process driven by chemotaxis, and was found to be involved in controlling the directional extension of pseudopods during migration (Stepanovic et al, 2005;Zhang et al, 2003). In mammalian cells, PKA has been shown to play a central role in actin-based cell migration through the differential regulation of Rac, Rho and Rap1 GTPases, as well as of VASP, PI3K, PAK and LIM kinases, at the leading edge of migrating cells (Chen et al, 2005;Howe, 2004;Howe et al, 2005;Jones and Sharief, 2005;Lim et al, 2008;Nadella et al, 2009;Paulucci-Holthauzen et al, 2009;Takahashi et al, 2013;Toriyama et al, 2012;Zimmerman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that WAVE2 makes a complex with PKA and acts as AKAP that recruits PKA at membrane protrusions. In addition to WAVE2, integrin ␣4 (37) and AKAP-lbc (38) have been reported to form a complex with PKA and recruit PKA to protrusions in colon carcinoma cells and CHO cells. Interestingly, AKAP-lbc ablation reduces but does not completely disrupt PKA localization at protrusions (38).…”
Section: Discussionmentioning
confidence: 99%